Seed predation food web, nutrient availability, and impact on the seed germination of Senegalia tenuifolia (Fabaceae) - Tuller, Juliana (2015)
Food web studies, which include qualitative and quantitative information about species interactions for all trophic levels in a specific community, are important tools to characterize the community structure, and to understand the role of species interaction in natural communities. With this aim, we collected fruits of Senegalia tenuifolia from a total of nine sites from three different areas in Minas Gerais, from June to August 2011. Fruits were collected and taken to the laboratory in special containers, to allow insect development and description. And then, we characterized the food web of insects associated with these seeds, and described interactions between these organisms and the host plant, and assessed the impact of insect attacks on seed germination with an experiment under controlled conditions. Additionally, we estimated the available NPK content and the Carbon:Nitrogen ratio in both fruits and seeds. In S. tenuifolia seeds, we have found 937 associated insects of 15 species structured in four trophic levels. We found two Bruchinae seed-feeders species: Merobruchus terani and Stator maculatopygus. We also have observed the seed-feeding hymenopteran species Allorhogas sp. 1 and Prodecatoma sp. 1, and hymenopteran parasitoids species such as Eupelmus sp.1, Lyrcus sp.1, Eurytoma sp.1, Horismenus sp.1, Chelonus sp.1, Aprostocetus sp.1, Eiphosoma sp.1 and an unidentified Pteromalinae. Considering quantitative food web metrics, our data have suggested low values of generality and high values of trophic vulnerability, besides others, which demonstrated how species interactions are specialized. The impact of seed-feeding insects on seeds was found severe and prevented their germination. Lastly, seeds contained higher NPK content than fruits. In conclusion, the seed predation food web supported by S. tenuifolia has depicted two different features: specialized species interactions, considering parasitoids and seed-feeding species, and, generalized species interactions, considering host-plant and seed-feeding species. Indeed, seeds are resources with high nutrient concentration supporting a rich and complex food web. Finally, S. tenuifolia seeds are directly impacted by seed-feeding insects, preventing them from germination, which could result in a negative effect on host-plant population.